Vyadhibala and its Assessment – A Narrative Review - padhi , Archana; mohanta , Sarita (International Research Journal of Ayurveda & Yoga, 2025)
Ayurveda is a comprehensive medical system based on ancient medicine. To become an expert and achieve dominance in clinical approaches, one must possess a thorough comprehension of science. In clinical medicine, the first stage is a thorough evaluation of the patient, which is followed by the planning of appropriate therapies. If a doctor starts treating patients without properly diagnosing the condition, achieves the desired result by accident, and does not become well-known. Conversely, a doctor will undoubtedly succeed if he gives medications following a correct diagnosis and develops the primary course of care after taking the morbidity of pathogenetic variables, strength, location, season, etc., into account.